Tectonics and mechanism of a spreading ridge subduction at the Chile Triple Junction based on new marine geophysical data - Matsumoto, Takeshi; Mori, Asuka; Kise, Shinichiro; Abe, Natsue (GEOCHEMICAL JOURNAL, 2013)
The Chile Triple Junction (CTJ), an RTT-type triple junction located at 46°13′ S, 75°48′ W off the western coast of Chile, is characterized by the subducting Chile Ridge, which is the constructive plate boundary that generates both the Nazca Plate and the Antarctic Plate. The ridge subduction mechanism and the regional tectonics around the CTJ were investigated primarily using marine geophysical data (topography, gravity, geomagnetic field and single-channel seismics) collected during the SORA2009 cruise (Cruise ID = MR08-06) by R/V MIRAI together with other cruise data from the National Geophysical Data Center. The segment of the ridge axis just before the subduction around the CTJ is associated with an axial deep covered with thick sediment unlike that seen in typical ridge crests. The profiles of both topography and the free air anomaly around the CTJ show quite different patterns from those of ordinary subduction zones. However, topographic features typical of a slow-spreading type ridge, including a median valley and both flanks, remain in the seaward side of the trench. Even after the subduction of the eastern flank, the topographic features of the western flank remain. A slight Outer Rise and an Outer Gravity High, which are common in the western Pacific area, were observed in an area far away from the CTJ on both Nazca and Antarctic plate sides. The geomagnetic anomaly pattern around the Chile Ridge near the CTJ shows that the estimated spreading rate decreases gradually towards the ridge crest. This suggests that volcanic activity diminishes gradually towards the subducting ridge axis. The lithosphere under the Chile Ridge might have amalgamated with the surrounding oceanic lithosphere due to heat loss after the cessation of volcanic activity. The oceanic lithosphere towards the trench also thickens rapidly due to heat loss. Consequently, shallow-angle subduction of the youngest and most immature oceanic plate occurs smoothly via slab-pull force without any resistance along the interface between the ...